Development of a Simultaneous Sulfadiazine, Sulfamethoxazole, and Tetracycline Antibiotic Level Determination Method with High-Performance Liquid Chromatography - Yanulia Handayani; Iswandi; Supriyadi (Natural Sciences Engineering and Technology Journal, 2023)
Sulfonamides and tetracyclines are a group of synthetic antibacterials that are widely used in veterinary practice for the treatment and prevention of infections in animals that can be consumed by humans. The purpose of this study was to determine the optimum conditions for High-Performance Liquid Chromatography for simultaneous analysis of sulfadiazine, sulfamethoxazole, and tetracycline and meet the validation requirements. The research method used is the HPLC method. The instruments used are Agilent 1220 Infinity II low-pressure dual-channel gradient valve, variable wavelength detector (VWD) BI detector, the column used is Agilent 5 TC-C18 (250 x 4.6 mm), motion phase A = acetic acid 0.08%: acetonitrile (9:1) and motion phase B = methanol with a flow rate gradient of 0.5 mL/minute and UV-VIS detector at wavelength 295 hm. The results showed that the method of determining the levels of sulfadiazine, sulfamethoxazole, and tetracycline met the requirements of selectivity, accuracy, precision, linearity, LOD, and LOQ and could be applied to fish samples. The accuracy parameter test obtained recovery results between 96.99%-103.16% at all sample concentration levels of 80%, 100%, and 120%. Testing the precision parameters showed that all sample concentrations were 100% repeated for 6 times replications, fulfilling the precision requirements, namely, the concentration of ≥10 ppm was < 7.3%. The linearity test showed that the correlation coefficient of sulfadiazine was 0.999, sulfamethoxazole was 0.999, and tetracycline was 0.998. LOD and LOQ values of sulfadiazine 1.15 ppm and 3.84 ppm, sulfamethoxazole LOD 2.51 ppm and LOQ 8.37 ppm, and tetracycline LOD 3.37 ppm and LOQ 11.22 ppm. Applications to fish samples were carried out by addition and obtained levels of 14.79 ppm sulfadiazine, 14.01 ppm sulfamethoxazole, and 45.05 ppm tetracycline.